Does stride length play a role in cricket fast bowling performance outcomes? An observational, cross-sectional study. Issue 5 (October 2016) - Spratford, Wayne; Kenneally-Dabrowski, Claire; Byrne, Sean; Hicks, Amy; Portus, Marc
The aim of this study was to determine the effect of delivery stride length on the performance outcomes of ball release speed, accuracy and ball release height within a large cohort of elite male cricket fast bowlers. Data for this observational, cross-sectional study were collected from national under 19, senior state and international level players over a four-year period. No statistically significant differences were found between the three stride length groups (short, medium and long). However, a functional difference in accuracy was evident between short and long stride length groups, with the long stride length group being less accurate (effect size (ES) = 0.8; ES confidence interval (CI) = 0.2–1.4). Therefore, it can be concluded, given the results of the current study and previous injury-related research, that in no way is it advantageous for bowlers to have a stride length that exceeds the recommended 75–85% of standing height.